Pengaruh Cash Turnover, Working Capitalturnover, Receivable Turnover, Dan Inventory Turnover Terhadap Return On Asset Pada Perusahaan Keramik Yang Terdaftar Di Bursa Efek Indonesia - Satriawaty Migang; Antika Irawan (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2019)
This research is meant to examine the influence of cash turnover, working capital turnover, receivable turnover, and inventory turnover to the return on assets in the Ceramic companies listed on the Indonesian Stock Exchange (IDX) in 2013-2017 periods. The independent variables in this study wer Cash Turnover, Working Turnover, Receivable Turnover, and Inventory Turnover, while for the dependent variable is Return On Assets. The samples are 5 companies which have been selected by using cross sectional. The financial statement data has been obtained from the Indonesian Stock Exchange (IDX). The research method has been done by using quantitative method and multiple linier regressions with the application instrument of SPSS (Statistical Product and Service Solutions). The result of this research shows that working capital turnover has an influence to the return on assests whereas the cash turnover, receivable turnover and inventory turnover do not have any influence to the return on assets. The value R square is 0,558 which shows that all of independent variables which are cash turnover,working capital turnover, receivable turnover and inventory turnover can explain the dependent variable is return on assets is 55,8% and remaining is 44,2% which is influenced by orther factors which are not included in this model.